2020
DOI: 10.1039/d0ra04704j
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput in-focus differential interference contrast imaging of three-dimensional orientations of single gold nanorods coated with a mesoporous silica shell

Abstract: Spherical AuNRs@mSiO2 have randomly oriented AuNR cores in 3D space, which could be resolved on the same focal plane by interference-based DIC microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Interestingly, Yoon et al reported the synthesis of discrete and uniformly silica-coated AuNRs with a finely tuned shell thickness by significantly suppressing the formation of undesired core-free NPs. [68][69][70] Based on the modified Lamer Theory, they adjusted the amount of silica precursor to suppress homogeneous nucleation and injected silica precursor to induce only heterogeneous nucleation. The authors were able to control the thickness of the silica shell with a high degree of precision, close to 1 nm; therefore, the rotational diffusion mode of NPs could be observed by simply controlling the silica precursor injection times (Figure 10a-c).…”
Section: Engineering Thickness Porosity and Anisotropy Of Silica Capp...mentioning
confidence: 99%
“…Interestingly, Yoon et al reported the synthesis of discrete and uniformly silica-coated AuNRs with a finely tuned shell thickness by significantly suppressing the formation of undesired core-free NPs. [68][69][70] Based on the modified Lamer Theory, they adjusted the amount of silica precursor to suppress homogeneous nucleation and injected silica precursor to induce only heterogeneous nucleation. The authors were able to control the thickness of the silica shell with a high degree of precision, close to 1 nm; therefore, the rotational diffusion mode of NPs could be observed by simply controlling the silica precursor injection times (Figure 10a-c).…”
Section: Engineering Thickness Porosity and Anisotropy Of Silica Capp...mentioning
confidence: 99%
“…Second, when drop-casting is used for sample preparation, AuNRs lacking the shell align parallel to a glass slide, resulting in tilting angles nearly identical to those of the glass slide (see Figure S1). On the contrary, when spherical AuNRs@ m SiO 2 are placed onto a slide, the AuNRs within the silica shell exhibit random 3D orientations within the identical focal plane (Figure A). , Therefore, high-throughput characterization of image patterns as well as optical properties for individual AuNRs having random 3D orientations within the identical focal plane can be accomplished, overcoming the drawbacks of the conventional gel matrix technique involving the scanning of embedded AuNRs in a vertical direction (Figures S2 and S3). , …”
Section: Resultsmentioning
confidence: 99%
“…Next, we examined the three fixed AuNRs@ m SiO 2 (Figure ) under DIC microscopy, specifically at 700 nm near their LSPR wavelength (Figure S12). High-throughput DIC orientation imaging of individual AuNRs within the spherical shell in the same focal plane was achieved (Figure S13), , and DIC signals from the AuNRs within the silica shell were used for investigating their characteristic optical properties. , To explore the dependence on wavelength and polarization, a rotational analysis of AuNR1@ m SiO 2 was conducted by incrementally rotating a stage in 10° steps from 0 to 360° at the LSPR wavelength. Figure A illustrates the definition of the polar angle θ and azimuthal angle φ of the AuNR in DIC microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the optical properties of gold nanoparticles are significantly affected by the morphological properties of individual nanoparticles, including their size and shape, the statistical distribution of the entire population of nanoparticles is expected to significantly affect their optical properties. For this experiment, we prepared five sets of gold nanorods with different aspect ratios (ARs), and according to their localized surface plasmon resonance (LSPR) peak wavelengths at 880, 843, 759, 714, and 648 nm, we labeled these sets as E1, E2, E3, E4, and E5, respectively (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%